Are interventional radiology and allied specialities neglected in undergraduate medical education? A systematic review - Emin, Elif Iliria (Ann Med Surg (Lond), 2019)
OBJECTIVES: Minimally invasive interventional approaches are gaining wider acceptance with several specialities incorporating such principles. Awareness and understanding of interventional principles require efficacious education and training methodologies. We performed a systematic review to identify all available interventional speciality learning modules or training opportunities available for undergraduate medical students. We also propose a standardised framework for relevant modules. METHODS: We searched PubMed and all Ovid databases with no language restriction for studies that report and evaluate interventional speciality educational modules or similar training initiatives. We followed a prospective protocol (PROSPERO registration: CRD42018110006). Internal and external validity of the included studies was assessed. Qualitative synthesis of data was performed to define performance improvement and/or motivation towards a career in an interventional speciality. RESULTS: Out of 6081 records, 17 studies met the inclusion criteria, 15 of which were focused on interventional radiology. More than half of studies (9/17) were surveys where student knowledge and interest were reported as poor. 5 out of 6 studies which assessed the effect of educational interventions concluded to improved knowledge or performance. Most surveys concluded that early exposure can increase interest towards such specialities, improve knowledge and relevant motivation. CONCLUSIONS: Few studies report teaching initiatives in interventional radiology and other interventional specialities, reflecting the poor relevant motivation and knowledge amongst medical students. Simple interventions e.g. introductory lectures and simulation sessions spark interest in students and also improve knowledge as proven in the case of interventional radiology. Standardisation of such efforts via a suggested framework, Strategy Development Framework for Interventional Radiology, can further optimise such outcomes.